Preterm and low birthweight as a risk for the development of children - Linhares, Maria Beatriz Martins; Carvalho, Ana Emília Vita; Bordin, Maria Beatriz Machado; Chimello, Juliana Thomazatti; Martinez, Francisco Eulógio; Jorge, Salim Moysés (Paidéia (Ribeirão Preto), 2000)
The aim of the present study consisted of assessing the impact of extremely pre-term low birthweight (